The cat's table - Ondaatje, Michael 1943-
With utter certainty, I can claim that I?ve never ever been remotely disappointed by a Michael Ondaatje title. Until now, alas. Here?s my very best advice to you about this, his long-awaited new title, The Cat?s Table: read it page by page for yourself only; do not choose the audible option, even as the venerable Ondaatje himself narrates. Really. At least with this work, Ondaatje?s voice unfortunately expresses a sense of detachment so visceral that bonding with the book?s protagonist proves difficult at best ?